Ivy + Bean bound to be bad - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2008)
Best friends Ivy and Bean learn that being very good, or very bad, can be a real challenge when they set out to become like a man Ivy heard about who was so pure of heart that birds and animals followed him.
Keywords: Behavior -- Fiction; Human-animal relationships -- Fiction; Neighbors -- Fiction; Family life -- Fiction